McDonald's 55 cent promotion - Robinson, David (London : SAGE Publications Ltd, 2017)
After decades of international success, by 1997, McDonalds faced slowing sales growth and stiff competition in the United States. Price promotion seemed like a good way to rekindle sales growth. However, in June 1997, McDonalds corporate management abruptly announced that it was cancelling its price promotion, "Campaign 55," which had been planned to last all year. The attention-getting pricing plan was to feature a different hamburger-sandwich each month at the bargain price of just $0.55 (in honor of the 1955 founding of the fast food chain). The promotion began with the companys flagship product, the Big Mac. Since the regular price of a Big Mac was close to $2, it was surprising that the company's loyal customers joined restaurant owners and howled in complaint about the "55" promotion.
Originally published in Robinson, D. (2011). McDonalds 55 cent promotion. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; McDonald's Corporation; Fast food restaurants -- Marketing; Fast food restaurants -- Prices; Consumer behavior